A novel and efficient address configuration for MANET. (20th June 2019) - Li, Yanli; Wang, Xiaonan
Summary: At present, one technical challenge of MANET is the address configuration, and another technical challenge is to deal with the network merging in order to ensure the address uniqueness in the merging network. This paper proposes a scheme to address these two issues. In the scheme, the MANET architecture is presented, and based on the architecture the address configuration algorithm is proposed. This algorithm employs an allocation variable to achieve the address configuration, and a node can ensure the address uniqueness without any interactions with other nodes. In order to effectively detect the network merging, this scheme proposes the generation algorithm of the MANET ID which uniquely identifies MANET. Based on this generation algorithm, the network merging algorithm is proposed. In this algorithm, only the nodes with the duplicate address perform the address reconfiguration, so the network merging cost and delay are reduced. This scheme is evaluated, and the results show that this scheme effectively improves the address configuration performance and the network merging performance. Abstract : This paper has the following contributions:1) MANET ID can effectively detect the network merging.2) An allocation variable can effectively achieve the address configuration.3) Only the nodes with the duplicate address perform the address reconfiguration, so the address uniqueness is ensured and the network merging cost and delay are reduced.